Floating Test (Rossipal) for Screening Patients with Fat Malabsorption - I. Mustadjab; Pitono Soeparto; Karyadi Karyadi (Paediatrica Indonesiana, 1980)
Floating test for fat malabsorption as outlined by Rossipal et al. has been done in 20 malnourished infants and in 25 infants suffering from minor illnesses who served as control. Concomitant lipiodol absorption tests were also performed in the malnourished group. Floating test seemed to be of use as screening test to establish the presence or absence of a definite steatorrhoea, but failed to determine the variations of abnormal fat absorption. It can be used as an alternate to lipiodol absorption test where lipiodol is not available or difficult to obtain.